2005
DOI: 10.1002/chin.200534338
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Amines in Food

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
166
1
21

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(190 citation statements)
references
References 1 publication
2
166
1
21
Order By: Relevance
“…According to the classifi cation of carcinogenic compounds, N-nitrosodimethylamine (NDMA), and N-nitrosodiethylamine (NDEA) belong to the group of the probable carcinogens, whereas N-nitrosodibutylamine (NDBA), N-nitrosopiperidine (NPIP) and N-nitrosopyrrolidine (NPYR) belong to the group of the possible carcinogens (Yurchenko and Mölder, 2005). What is more, Karovičová and Kohajdová (2005) claim that putrescine (PUT) from ornithine, cadaverine (CAD) from lysine, spermine (SPM) and spermidine (SPD) from putrescine can be the precursors of carcinogenic N-nitrosamines. For example, CAD can be converted into N-nitrosopiperidine (NPIP) and PUT, SPM, SPD can form N-nitrosopyrrolidine (NPYR).…”
Section: Introductionmentioning
confidence: 99%
“…According to the classifi cation of carcinogenic compounds, N-nitrosodimethylamine (NDMA), and N-nitrosodiethylamine (NDEA) belong to the group of the probable carcinogens, whereas N-nitrosodibutylamine (NDBA), N-nitrosopiperidine (NPIP) and N-nitrosopyrrolidine (NPYR) belong to the group of the possible carcinogens (Yurchenko and Mölder, 2005). What is more, Karovičová and Kohajdová (2005) claim that putrescine (PUT) from ornithine, cadaverine (CAD) from lysine, spermine (SPM) and spermidine (SPD) from putrescine can be the precursors of carcinogenic N-nitrosamines. For example, CAD can be converted into N-nitrosopiperidine (NPIP) and PUT, SPM, SPD can form N-nitrosopyrrolidine (NPYR).…”
Section: Introductionmentioning
confidence: 99%
“…4.1% were found to have tyramine in the range of 100-500 mg/l. The results are threatening if compared to the legal limits set by the Nutritional Codex of the Slovak Republic which says the maximum tolerable limit of tyramine in cheese in 200 mg/kg (Karovičová & Kohajdová 2003). The European Union has set the regulations for levels of histamine.…”
Section: Resultsmentioning
confidence: 99%
“…Biogenic amines, the so called natural amines with physiological significance, belong to this group of substances (Karovičová & Kohajdová 2003). Biogenic amines, which are produced in a number of foods, are organic bases with an aliphatic, aromatic, or heterocyclic structure (Alvarez et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They can, therefore, become a problem in traditionally fermented food products especially if present initially in high numbers [81]. Production of biogenic amines seems to be unfavorable activity of enterococci in fermented dairy products, because biogenic amines have been associated with a number of food poisoning episodes [82]. It has been observed that the prolifi c growth of enterococci in milk and milk products leads to the formation of signifi cant levels of biogenic amines [4,43,83].…”
Section: Undesirable Activities Of Enterococcimentioning
confidence: 99%
“…Safe strains of enterococci that can be used in food and as probiotics ideally should possess neither any of virulence factors, nor should be able to acquire antibiotic resistance gene [8]. Furthermore, biogenic amines producing strains are also not preferable in food [82]. Opsonophagocytic killing is considered to be additional and an important test to assess the safety of enterococcal strains.…”
Section: Safety Assessment Of Enterococcimentioning
confidence: 99%